Co-circulation of dengue virus type 3-genotype I and type 2-Cosmopolitan genotype in 2018 outbreak in Dhaka, Bangladesh. (January 2020) - Ahmad, F.U.; Paul, S.K.; Aung, M.S.; Mazid, R.; Alam, M.; Ahmed, S.; Haque, N.; Hossain, M.A.; Paul, S.; Sharmin, R.; Kobayashi, N.
Abstract: Dengue virus (DENV) that caused an outbreak in Dhaka, Bangladesh during 2018 was analysed phylogenetically. DENV samples were classified into type 2-Cosmopolitan genotype (54%) and type 3-genotype I (46%), indicating co-circulation of two DENV types and resurgence of type 3 associated with genotype replacement.